Determination of the possibility of development of threatening condition in patients with diabetic ketoacidosis - Lysenko, Viktor; Bryk, Ruslan; Vysotska, Olena; Porvan, Andrei (ScienceRise: Medical Science, 2017)
The aim of the research was to create a mathematical model for determining a possibility of the threatening condition development in patients with diabetic ketoacidosis using methods of mathematical statistics. Methods. There were examined 43 patients with diabetes mellitus decompensation, who underwent intensive therapy by the offered method. Patients were divided in two groups depending on the presence of the threatening condition: group 1 – patients without hepato-intestinal dysfunction (12 persons); group 2 –patients with hepato-intestinal dysfunction (31 persons). All indicators were registered at admission to the department of intensive care at first, third and fifth day after the treatment. The method of logistic regression was used for constructing the mathematical model. Results. There were revealed 5 most important indicators for determining the threatening condition, used as prognostic factors for estimating the complications probability. The model for assessing the data, used for ROC-analysis, was constructed. Conclusions. The elaborated mathematical model of the possibility of the threatening condition development in patients with DKA allows to diagnose not only dangerous tendencies in real time, but also to use medical strategies for preventing and restoring hepato-intestinal and multiple organ dysfunction in these patients